Struktura retoryczna Psalmu 77 i jego interpretacja - Mrozek, Kinga (Poznańskie Studia Teologiczne, 2007)
The article presents an analysis of one of the Psalms of Asaph - Ps 77. The main purpose of the study is to show the dependence between the structure of the text and its interpretation, the impact of text division on ascertaining its message. With this aim in view different propositions of exegetes are set forth, their standpoints falling into two groups. On the one hand they divide Ps 77 according to the following criteria: the ‘selah’ pause or the generic features of the text - this approach results in demonstrating the nonuniformity of Ps 77. On the other hand, some exegetes claim that the analyzed text contains features that allow us to consider it as a uniform whole. The division of Ps 77 proposed in the article is based firstly on formal criteria and secondly on content criteria. Finally, a synthesis of both types of division is achieved and serves as a basis of interpretation. In this way it becomes possible to show: the dynamism of the content of Ps 77, its major themes, its reflective character, the image of a gracious but at the same time also mighty God, and the parenthetical features of the psalm.